Farelo de girassol na alimentação de aves Isa Label em fase de postura em ambiente equatorial - Oliveira, Vanessa Raquel de Morais (Universidade Federal Rural do Semi-Árido, 2014)
ABSTRACT - The objective of this study was to evaluate production and egg quality of laying hens Isa Label fed different levels of sunflower meal, the infrared thermography and productive characteristics of laying hens in semi-intensive production system in tropical conditions. One hundred and twenty-eight laying hens with early age of 28 weeks, during 16 weeks of evaluation, distributed in a completely randomized design in 16 boxes with 8 birds per experimental unit were used. The treatments consisted in a control diet (RCO) and three diets containing sunflower meal in substitution for soybean meal, based on the crude protein levels of 10, 20 and 30% (FG10, FG20, FG30) , being all diets based on the nutritional requirements of the laying hens. During the total period of review there was no difference (p> 0.05) between the levels of substitution of crude protein of soybean meal by sunflower meal on productive performance and egg quality of laying hens. The economic analysis of dietary treatments decreased the price per kilogram of feed (1.49, 1.46, 1.44, 1.41 reais, respectively) as replaced by 0, 10, 20 and 30% levels crude protein soybean meal by sunflower meal. The FG30 treatment compared with other treatments was better, it showed better Average Cost Index (ACI) and Economic Efficiency Index (EEI). The egg production was not influenced with the temperature increase over the weeks, obtaining higher production values between the 39th and 42nd weeks of age, which is due to genetic effects of Isa label. In the evaluation of the surface temperature by infrared thermography, laying hens showed higher average temperature in the neck region (39.35° C), followed by face (38.47° C), feet (37.15° C) and feathered area (31.56° C). Therefore, taking into consideration the viability was observed, the replacement of soybean meal by sunflower meal in balanced diets for broilers Isa label in laying phase can be used
Sunflower meal for feeding of Isa Label laying hens in an equatorial environment
Keywords: laying hens; Economic analysis; Helianthus annuus; infrared thermography; Galinha caipira; Análise econômica; Helianthus annuus; Termografia infravermelha; CIENCIAS AGRARIAS::MEDICINA VETERINARIA